ADDITION OF FLY ASH TO THE FIBER COMPOSITE GLASS ON COMPOSITE FUEL RESISTANCE PROPERTIES - Bahas Loh Kertabait (Institut Teknologi Dirgantara Adisutjipto, 2020)
The process of making composites into several main stages, namely preparation of tools, cutting of specimens. Then the base (glass) is cleaned and coated with molding wax and PVA. Mix the resin with the addition of variations of fly ash 0%, 10%, 20% and 30%. Next, apply resin and glass fiber to the base (glass) for up to 3 layers then press it. After 12 hours remove the specimen and cut it to size